National Stereotypes in the Cultural Scenery of Modern Journalism (Proceedings of Southern Federal University. Philology, 2019)
Irina V. Erofeeva, Olga A. Filshina (Chita, Russian Federation)The article presents the linguoculturological analysis of national stereotypes in the discourse of modern journalism. The empirical base of the research consists of more than 500 journalistic texts of different formats and genres. The cultural scenery of the media text is the whole system of key values that reflect the spectrum of people’s life in a certain area and broadcast in the paradigm of «past-present-future». The stereotypes as cognitivelinguistic structures are supported by addresser’s and addressee’s background knowledge, they involve prototext meanings a priori topical and requested by a mass audience. In authors’ view, linguocultural stereotypes in the media text space develop their meanings due to the use of topoi – the steady speech formulas, problems and plots, scenario markers characteristic of a national worldview. The representation of national stereotypes is not only economically feasible, but also it provides the national identification which is necessary for society and allows to realize the cultural-hereditary function of the media.Key words: national stereotypes, journalism, media text, national identity, linguistic personality, representation, topos.DOI 10.23683/1995-0640-2019-4-200-208